Break every rule [large type] - Freeman, Brian, 1963- (Blackstone Publishing, 2024)
Tommy Miller, a man with deadly skills, hides in Florida under a false identity. After he is set up on an overseas mission, he's on the run from the government that betrayed him. When his wife and daughter are abducted, his ghosts may be catching up with him. But his wife conceals secrets of her own. To find his family, he must follow clues she left behind.